Interdisciplinary Approach of Pygmy Musics - (:unkn) unknown (My University, 2007)
The author presents the music of two Pygmy cultures, Aka from Central Africa, and Baka from Cameroun. She combines musicological and ethnological concepts with notions from acoustical phonetics and ethnolinguistics. The analysis of the musical system and the study of vernacular concepts lead to the categorization of the entire musical repertoire. This method reveals how the musical structure takes an essential part in the symbolic organization of societies with oral tradition. The complete study of the borrowing of a ritual from a neighbouring society illustrates the variability of the Baka culture. This ethnomusicological research contributes to the sharpening of musicological tools. It is imbedded in an interdisciplinary network that aims for a better understanding of Pygmy cultures and for the history of interethnic contact and migrations in Central Africa.
Keywords: African Research